Parental financial socialization on emerging adulthood: A dual perspective study - Akbar, Rasyidi Faiz; Kautsar, Achmad; Kusumawati, Nunik Dwi; Nihaya, Ina Uswatun; Putra, Syaifurrizal Wijaya; Ramadhani, Bima Yatna Anugerah; Nadia, Fiona Niska Dinda (CV ODIS, 2024)
This study investigates the impact of parental financial socialization on the financial behaviors and attitudes of emerging adults, considering both parental and child perspectives. It examines direct teaching, role modeling, and the quality of financial relationships in shaping financial outcomes. Using a quantitative purposive sampling method, data were collected from 524 participants through structured questionnaires assessing parental financial teaching, attitudes, and behaviors. Structural equation modeling was used to analyze these relationships. Findings reveal that parental direct teaching and role modeling significantly influence emerging adults' financial attitudes and behaviors. A positive financial relationship between parents and children enhances financial socialization practices. Emerging adults reporting higher levels of parental guidance and role modeling exhibit better financial behaviors and more responsible attitudes. The study also identifies significant mediating effects of financial attitudes on the relationship between parental socialization practices and behaviors. This research highlights the dual influence of parental teaching and role modeling on young adults' financial outcomes and underscores the importance of supportive financial relationships. It offers insights into the mechanisms through which parental behaviors shape financial competence, providing a foundation for targeted financial education programs and policies.